Self-conditioning adhesives in pediatric dentistry: an integrative literature review (Research, Society and Development, 2022)
As clinical time must be taken into account in pediatric dental care, the use of self-etching accessories is the best alternative for restorative procedures in this population. Cons suitable accessories, which require a conditioning time, self-etching accessories and time separators with the number of steps and the number of steps required. However, this theme is still not clear in the literature. Thus, the objective of this integrative literature review was to compare, in relation to their clinical performance and their adhesive properties, self-etching accessories compared to the performance of restorations compared to primary teeth. The search was performed on Pubmed, Google Scholar and EBSCOHost with the descriptors “dentin-bondin agents OR dentin-bonding system” AND “deciduous OR primary teeth” AND “self-etch adhesive OR self-etch system” Per studies from the last five years . Thirty-six articles were obtained and five were selected. In only one study, self-etching adhesives and performance differences between their self-etching characteristics and performance differences between the evaluated characteristics. Therefore, studies selected for the selected studies, randomly selected and with study time are considered better that are not more rigid and that are more rigid in randomized trials and that have been considered as time period.